Sickle Cell Disease and Other Risk Factors for Pediatric Arterial Ischemic Stroke: A Systematic Review and Meta-Analysis - Cecilia Putri Tedyanto; Laura Wihanto; Eric Hartono Tedyanto; Anna Marita Gelgel; Ni Made Dwita Pratiwi (Annals of Child Neurology, 2024)
Purpose The incidence and mortality rates of arterial ischemic stroke (AIS) among pediatric patients have been frequently reported. While pediatric stroke can have multiple severe effects, its risk factors have not been methodically examined. This systematic review and meta-analysis were completed to summarize the existing evidence regarding risk factors for AIS in pediatric patients. Methods To gather relevant articles published in the past 15 years, searches were conducted of PubMed and Scopus. Multivariate odds ratios (ORs) and 95% confidence intervals (CIs) were analyzed using Review Manager 5.4. Results From the initial screening of 507 articles, five articles comprising a total of 1,423 participants were selected for qualitative analysis. Two of these additionally underwent quantitative analysis. Among the total participants, 1,108 children with AIS (77.9%) had arteriopathy as the underlying disease. Types of arteriopathy included moyamoya disease (24.28%), arterial dissection (23.29%), focal cerebral arteriopathy (16.16%), and vasculitis (14.71%). The meta-analysis revealed that being between 6 and 9 years of age (OR, 2.19; 95% CI, 1.76 to 2.73; P<0.00001) and having sickle cell disease (OR, 3.46; 95% CI, 2.38 to 5.05; P<0.00001) were associated with arteriopathy in pediatric AIS. Conclusion Arteriopathy is the most common risk factor for AIS in pediatric patients, and in turn, an age of 6 to 9 years and sickle cell disease are risk factors for arteriopathy within this demographic.